Sosialisasi Manajemen Rantai Pasok Berkelanjutan UMKM di Desa Tegallega, Karawang - Fety Nurlia Muzayanah; Rediawan Miharja; Isro’iyatul Mubarokah; Muhammad Gibran Almanfarisi; Derisa Hendriyanti (I-Com: Indonesian Community Journal, 2024)
Tegallega Village is one of the villages in Ciampel Sub-district, Karawang Regency. Tegallega Village has several potentials and problems, especially in the economic sector. In the economic sector, Tegallega Village has the potential to develop MSMEs from KWT. The flagship products of Tegallega Village are gadung chips and banana chips. Unfortunately, these MSMEs in Tegallega Village still have several problems, such as not yet having a legal entity and still lacking product development and marketing strategies. Currently, product marketing is still limited to the surrounding area and still does not have optimal supply chain management to keep production running throughout the year. The method used in this activity consists of the preparation and implementation stages of socialisation. This activity provides understanding and knowledge for MSMEs about sustainable supply chain management and Tegallega Village MSME players can map their business supply chain management to determine operational strategies in reducing supply chain futility from upstream to downstream.